Quranic approaches in moral education: Curriculum for Islamic education at the secondary level in the West Bank Palestine as a case study / Mohammed A. M. Ataya - Mohammed A. M., Ataya (2017)
This study presented the Quranic approaches towards moral education. Five Quranic approaches were introduced for this purpose, namely: storytelling, dialogue, persuasion and intimidation, proverbs, and examples. The definition, understanding, and the educational impact of each were explained with three Quranic evidences. The prophetic applications of these approaches were illustrated as well. The discussion of the educational conditions associated with the implementation of the curriculum emphasized on the need of the integration between the Islamic courses and other courses offered to the students at different levels. Emphasis was also placed on the importance of teacher preparation, the importance of the usage of variety of methods and activities associated with the curriculum, and the importance of the adequacy of the time allocated for teaching Islamic studies. It further demonstrated the impact of the school and non-school environment in building student's morality. It sheds light on the need for integration of all factors to achieve the proper construction of the student’s moral personality. After grounding the research theoretical framework, the implication was made on the Islamic educational curriculum for the secondary level in Palestine. A descriptive analytical analysis was performed on the curriculum illustrating its comprehensive coverage of all elements of moral education. Additionally, it discussed how this curriculum treats the ethical and moral aspects in the student's personality. The impact of the methods and activeties associated with the curriculum in achieving its objectives was discussed. To promote the study, an empirical study was carried out by distributing a questionnaire to 40 male and female secondary school teachers at Palestinian schools in the West Bank. The questionnaire focused on teachers’ perceptions towards the usage of the Quranic approaches in their curriculum and methods of teaching. The findings of this study revealed the large similarity between the findings of curriculum analysis, which indicated significant weakness in the usage of proper educational methods, and the findings of questionnaire analysis which emphasizes the need of revising the Palestinian curriculum to cope with the Quranic approaches on moral treatment in order to be able to build a moral generation who are capable to fulfill their duty towards country and nation.